On the uniqueness of ARCH processes - Kazakevičius, Vytautas; Leipus, Remigijus (Lietuvos matematikos rinkinys, 2007)
In this note we prove the uniqueness of the solution to ARCH equations under conditions, which are weaker than in some earlier results.
Keywords: ARCH process; strictly stationary solution